O19.2 Bridging of neisseria gonorrhoeae across diverse sexual networks in the HIV PrEP era. (14th July 2019) - Williamson, Deborah; Chow, Eric; Gorrie, Claire; Ingle, Danielle; Easton, Marion; Seemann, Torsten; Taiaroa, George; Grad, Yonatan; Kwong, Jason; Fairley, Christopher; Chen, Marcus; Howden, Benjamin
Abstract : Background: Despite 'best effort' public health measures, the incidence of gonorrhoea is increasing in many countries. Recently, whole genome sequencing (WGS) has been used to investigate transmission of Neisseria gonorrhoeae, including antimicrobial-resistant (AMR) lineages, but to date, most studies have not combined genomic data with detailed patient-level information on sexual behaviour to define the extent of transmission across population subgroups ('bridging'). Methods: We performed an observational study and undertook WGS and bioinformatic analysis on all cultured clinical isolates of N. gonorrhoeae in the state of Victoria, Australia, from January to December 2017. Antimicrobial susceptibility testing was performed on all isolates, and detailed epidemiological data was obtained, including data on sexual orientation, HIV status, use of HIV pre-exposure prophylaxis (PrEP), sex work, and overseas travel. Epidemiological associations were made with dominant genetic clusters of N. gonorrhoeae. Results: A total of 2, 186 isolates were sequenced from 2, 055 patients, 86·3% of whom were male. We identified eleven dominant genetic clusters, containing thirty or more patients, with the largest cluster comprising 181 patients. There was extensive bridging of clusters between men who have sex with men (MSM) and heterosexuals, with bisexual males identified in seven of the major clusters. Eight major clusters contained HIV-positive and HIV-negative patients (including individuals receiving PrEP). We also identified transmission of a novel azithromycin-resistant clone, associated with a mosaic mtr locus. Conclusion: To our knowledge, our study is the first to combine WGS with comprehensive individual-level behavioural risk data, providing verification for transmission of multiple gonococcal lineages within and across distinct sexual networks. Application of these methods in real-time will allow gonorrhoea transmission and antimicrobial resistance to be tracked, with 'hotspots' identified for interventions aimed at improving gonorrhoea control. Disclosure: No significant relationships.